Pendidikan dan Pelatihan Tentang Pencegahan dan Perawatan Gigi Berjejal Kepada Jemaat Gereja Bethel Indonesia HMJ Greenville, Jakarta - Hapsari Andayani, Lia; Kusnoto, Joko; Piona Sahelangi, Olivia; Dwimega, Arianne; Ratnasari, Dina (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Crowded teeth are one of the dental and oral health issues that need attention in Indonesia. Crowded teeth can be caused by genetic factors, growth abnormalities, or bad habits formed from a young age. Knowledge about the causes, impacts, prevention, and treatment of crowded teeth is important to enhance from an early age. The Community Service activity by the Faculty of Dentistry team from Trisakti University aims to enhance the knowledge and skills of the GBI HMJ Jakarta congregation in recognizing, preventing, and treating dental crowding issues. This activity involved 34 members of GBI HMJ Jakarta, consisting of administrators and the community. The educational material provided consists of the causes, effects, prevention, and treatment of crowded teeth. The training materials include simulations on how to brush teeth and use dental floss. The evaluation of the activity implementation shows an increase in knowledge with a significant difference in the average pre-test and post-test scores (p=0.000). This increase in knowledge is expected to reduce the negative impact of dental and oral health issues, particularly crowded teeth, in the community.